Exploring three-mediation paths of transformational leadership and innovative work behavior - Udin, Udin; Dananjoyo, Radyan (Journal of Social Economics Research, 2024)
The main goals of this in-depth study are to look at how transformational leadership (TL) affects psychological empowerment (PE), knowledge sharing (KS), work passion (WP), and innovative work behaviour (IWB), and how PE, KS, and WP affect the relationship between TL and IWB. The samples in this study were obtained by purposive sampling. This study employed quantitative data, which were collected through questionnaires distributed online to the respondents from functional staff and line managers working in the stone milling company in Indonesia. The 193 respondents' data were subsequently analyzed via Structural Equation Modeling (SEM), utilizing SmartPLS 3.0 as the analytical tool. This study’s results concluded that TL directly had no significant effect on IWB. In contrast, this study proved that TL significantly affected PE, KS, and WP. In addition, this study also revealed that there was a significant effect of PE, KS, and WP on IWB. According to the obtained findings, TL often empowers employees by fostering a sense of competence and autonomy, creating an environment where knowledge sharing is valued, and inspiring employees to have a deep sense of passion for their work. This, in turn, may lead to the exchange of new ideas and insights, contributing to innovative work behavior within the organization.